Specificity Of Pedagogical Communication - Ismailova Zukhra Karabaevna; Khashimova Masuda Kamilzhanovna; Potorochina Ksenia Sergeevna (Genius Journals, 2022)
This article discusses the issue of pedagogical communication, the specifics, types, requirements and significance of pedagogical communication, the norms and culture of communication of the teacher, the styles of communication and the structure of pedagogical communication, analyzes the problems stemming from non-compliance with the rules of pedagogical communication
Keywords: Communication; Perception; Verbal; Non-Verbal